Mental fatigue in golf: A systematic review. - Xiaoyang Pan; Kim Geok Soh; Wan Marzuki Wan Jaafar; Kim Lam Soh; Nuannuan Deng; Shudian Cao; Mingtian Li; Huange Liu (PLoS ONE)
Mental fatigue, or cognitive fatigue, is a multi-aspect of exhaustion resulting from prolonged engagement in mentally demanding tasks, characterized by diminished energy, mental exhaustion, and distraction, which can adversely impact various aspects of golfers' performance. However, there are still limited systematic reviews on the interaction between mental fatigue and athletes' performance in golf. This study aims to provide a comprehensive analysis of the correlation between mental fatigue and golf and demonstrate the current state of research and characterization of research in the field. The systematic review was conducted using a PRISMA flow chart, with thorough literature searches across PubMed, Web of Science, SPORTDiscus, Scopus, and China National Knowledge Infrastructure (CNKI) databases. The quality of the literature was assessed using Qualsyst. The study summarized findings from 10 articles on the interaction between mental fatigue and athletes' performance in golf. It indicates that mental fatigue is influenced by factors such as duration of play and walking distance, with prolonged golf tasks inducing mental fatigue. Mental fatigue directly affects golf performance, including the overall score for 18 holes, iron club accuracy, drive distance, and especially impacts putting performance. However, the results of these studies are limited and one-sided because studies conducted on driving ranges or in laboratories focus only on putting performance and ignore other golf skills. The study on the effects of mental fatigue on iron accuracy and driving distance was conducted under competitive conditions on an outdoor golf course, making it impossible to eliminate confounding factors. The lack of intervention studies on other specific golf skills may limit a comprehensive understanding of the impact of mental fatigue on golf performance. Trial registration Systematic Review Registration: [https://inplasy.com/][INPLASY202410111].